Pengaruh Citra Merek Dan Kesesuaian Harga Terhadap Loyalitas Pelanggan(Survei Pada Pengguna Smartphone Di Kalangan Anak Muda) - Cahyasari, Anindya Devira; , Ihwan Susila, SE., M.Si.,Ph.D (2016)
In the face of an increasingly marketing forward in the field of smartphones the company should compete and compete healthily to always produce smartphone with these advantages in the smartphone. This research aims to analyze the effect of brand image and price compliance against customer loyalty in purchasing smarphone in young people. This study derives directly onsite research using questionnaires with data using the 150 respondents within two weeks. The Multiple analysis results, Y = 0, 755X1 + 0, 386X2. The most influential independent variable toward dependent variable is the variable brand image (0.755) and followed by a variable compliance rates (0.386). T test results proved that all the variables (the brand image and the price fairness) a positive effect towards the dependent variable the smartphone purchase customer loyalty among young children. Determination of coefficient data (adjusted R 2) obtained for 0.290. This means 29.0% customer loyalty can be explained by the independent variable, while the remaining 71.0% influenced by other variables not examined in this study. Keyword: customer loyalty, brand image, price, price fairness